Enhancing a 3D Printer with Online Access - Andrade, T. F.; Abreu, P.; Restivo, M. T.; Chouzal, M. F.; Santos, B. F.; Rodrigues, J. (International Journal of Interactive Mobile Technologies (iJIM), 2017)
This paper looks at different ways of providing a RepRap 3D printer with online access and remote control to be operated from multiple devices including mobile devices. Different technological solutions that can be used with distinct printers are identified and tested. The selected and implemented remote access solution is described and examples of printed parts are presented. Reference is made to MSc theses that have been supported by this lab facility.